Effect of preharvest paclobutrazol and nitrogen fertilizers on the sprouting performance of ‘median’ potato seed G0 tuber - Hamdani, Jajang Sauman; Budiarto, Rahmat; Nuraini, Anne; Ramadani, Selika Fitrian (Universitas Padjadjaran, 2025)
Various intensifications of potato cultivation, such as the provision of paclobutrazol and nitrogen (N) fertilizer, are thought to impact the quality of the seeds produced. This study aims to evaluate the effects of different N fertilizer doses and paclobutrazol concentrations applied in the preharvest period on the sprouting performance of G0 potato tuber seeds after storage. Nine treatment combinations, each repeated three times, were tested, using 50%, 100%, and 150% of the recommended N dose and paclobutrazol concentrations of 50, 100, and 150 part per million (ppm), applied at 30 and 45 days after planting, respectively. The interaction effect between N fertilizer and paclobutrazol concentration was not significantly affected on all observed variables. Preharvest application of 100% N fertilizer produced the largest seedlings, indicated by the highest shoot length at 56 and 74 days after storage. Preharvest application of 150 ppm paclobutrazol produced the highest shoot length, shoot emergence rate, and seedling dry weight than other treatments. The present study implied the importance of preharvest N and paclobutrazol for improving the sprouting performance of G0 potato seed tuber.